Evaluasi Kebijakan Perlindungan Konsumen dan Tertib Niaga di Dinas Perindustrian dan Perdagangan Provinsi Bali - Suari Andini, Putu Ita; Winaya, I Ketut; Sastra Wijaya, Komang Adi (CITIZEN CHARTER, 2018)
ABSTRACT Consumer protection policies have not been carried out optimally, such as the lack of socialization and the absence of BPSK to resolve consumer problems outside the court. Therefore the researcher wants to evaluate the UUPK related to consumer protection policies in Bali Province. This research was conducted using descriptive qualitative, data collection techniques such as in-depth interview, observation and documentation. The indicator that used in this research is effectiveness, responsiveness, efficiency, and accuracy. The conclusions of this study are measured based on these four indicators, namely that the function of Law Number 8 of 1999 has not been maximized in terms of protecting consumers. Keywords: Evaluation, Policy, Consumer Protection